COMBINED HAMARTOMA OF THE RETINA AND RETINAL PIGMENT EPITHELIUM AT PEDIATRIC AGE: Surgical Versus Conservative Approach. Issue 2 (February 2023) - Ozdek, Sengul; Ucgul, Ahmet Yucel; Hartnett, M. Elizabeth; Akdogan, Muberra; Sen, Parveen; Bhende, Muna; Besirli, Cagri Giray; Karacorlu, Murat; Dedania, Vaidehi; Parolini, Barbara; Mittal, Sangeet; Banker, Alay; et al.
Abstract : Supplemental Digital Content is Available in the Text. This multicenter study demonstrates that pars plana vitrectomy with membrane peeling results in more favorable visual and anatomical outcomes compared with observation in pediatric patients with combined hamartoma of the retina and the retinal pigment epithelium, with an average follow-up of 36.2 months. Abstract : Purpose: To report outcomes of pediatric patients with combined hamartoma of the retina and the retina pigment epithelium followed up conservatively or after pars plana vitrectomy. Methods: This retrospective multicenter study included 62 eyes of 59 pediatric patients with combined hamartoma of the retina and the retina pigment epithelium from 13 different international centers with an average age of 7.7 ± 4.7 (0.3–17) years at the time of the diagnosis and having undergone pars plana vitrectomy or followed conservatively. At baseline and each visit, visual acuity values, optical coherence tomography for features and central foveal thickness, and tumor location were noted. Lesions were called as Zone 1, if it involves the macular and peripapillary areas, and the others were called as Zone 2 lesions. Results: Twenty-one eyes of 20 patients in the intervention group and 41 eyes of 39 patients in the conservative group were followed for a mean of 36.2 ± 40.4 (6–182) months. Best-corrected visual acuity improved in 11 (68.8%) of 16 eyes in the intervention group and 4 (12.9%) of 31 eyes in the conservative group ( P < 0.001). The mean central foveal thickness decreased from 602.0 ± 164.9 µ m to 451.2 ± 184.3 µ m in the intervention group, while it increased from 709.5 ± 344.2 µ m to 791.0 ± 452.1 µ m in Zone 1 eyes of the conservative group. Posterior location of tumor, irregular configuration of the foveal contour and ellipsoid Zone defect in optical coherence tomography, subretinal exudate and prominent vascular tortuosity were associated with poor visual acuity. Conclusion: Vitreoretinal surgery is safe and effective in improving vision and reducing retinal distortion in Zone 1 combined hamartoma of the retina and the retina pigment epithelium in children.